INFLUENCE OF TEACHERS SERVICE COMMISSION INCENTIVES ON TEACHERS’ PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN MIGORI COUNTY, KENYA - Atis, Omollo; Getange, Dr. Kennedy N.; Otengah, Prof. Wilson A. P. (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
The study sought to establish the influence of Teachers Service Commission incentives on teachers’ performance. The study adopted cross sectional survey design with a population of 3010 teachers who are the main respondents, 271 secondary school principals and 10 Teachers Service Commission Sub-County Directors of Education. Simple random sampling pegged at 30% was used to select 81 principals, 10 TSC Sub-County Directors of education through purposive sampling and 357 teachers from Krejcie and Morgan table, making a total of 448 respondents. The research questionnaires were administered to teacher and the principals, Focus Group Discussion to the teachers while the interview guide was used to collect data from TSC Sub-County Directors of Education. Piloting, involving 10% from each category of the respondents was done to establish validity and reliability of the research questionnaires and 36 teacher, 8 principals and 2 Sub-County Directors of Education were included. Validity was determined by supervisors and experts in Educational Management and foundation department. Test-retest method was used to test reliability and Pearson’s product moment correlation coefficient was further used to determine the reliability coefficient of .70 and above ascertaining the reliability of the instruments. Quantitative data was analysed using descriptive and inferential statistics where; frequency counts, percentage, mean and standard deviation was used, while qualitative data was coded, transcribed and organized thematically.. The study established that; Incentives offered by the employer can motivate the teachers with overall mean rating of 2.45. From the findings, the null hypothesis stated was rejected. The findings of the study may be of value to the Education developers and stakeholders to help improve the reward system and invest significantly on the teachers who enhance improvement and the best results on learners’ academic achievements.